A máscara, incorporação da exterioridade, exclusão e controlo da interioridade, reforço da identidade - Bastos, José Gabriel Pereira (Trabalhos de Antropologia e Etnologia, 2020)
“Masks and Masquerades” are approached not as a thematic subject but as a strategic object that allows to test the heuristic dimension of a structural-dynamic challenge, which is based in the detection of the failure of earlier ‘solutions’ presented. In societies against the state, the tribal dimension of these processes is thought of as a system of variants within which gender, inter-generational and inter-ethnic tensions are traded, in favor of the ‘society of men’ and of ‘male domination’. The emergence of the state as the Great Mask of the group, and its rapid transformation, hiding or marginalizing those manifestations, requires rethinking the historical dimension as structured by a system of transformations in the direction of contexts of increasing complexity.